2020
DOI: 10.1002/1873-3468.13917
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting glycosphingolipids for cancer immunotherapy

Abstract: Aberrant expression of glycosphingolipids (GSLs) is a unique feature of cancer and stromal cells in tumor microenvironments. Although the impact of GSLs on tumor progression remains largely unclear, anticancer immunotherapies directed against GSLs are attracting growing attention. Here, we focus on GD2, a disialoganglioside expressed in tumors of neuroectodermal origin, and Globo H ceramide (GHCer), the most prevalent cancer-associated GSL overexpressed in a variety of epithelial cancers. We first summarize re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 125 publications
(191 reference statements)
0
23
0
Order By: Relevance
“…Globo H is a prevalent cancer-associated glycosphingolipid and is overexpressed in many cancers of epithelial origins (e.g., breast, ovary, uterus, prostate, lung, colon, and liver cancers) [ 26 ]. Currently, there are several ongoing clinical trials on immunotherapies targeting globo H. Immunohistochemistry studies have demonstrated the presence of Globo H in 33% of MTCs, but not in normal thyroidea or benign thyroid lesions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globo H is a prevalent cancer-associated glycosphingolipid and is overexpressed in many cancers of epithelial origins (e.g., breast, ovary, uterus, prostate, lung, colon, and liver cancers) [ 26 ]. Currently, there are several ongoing clinical trials on immunotherapies targeting globo H. Immunohistochemistry studies have demonstrated the presence of Globo H in 33% of MTCs, but not in normal thyroidea or benign thyroid lesions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the various biological functions, sphingolipids and their derivatives have been studied for therapeutic applications of diverse diseases such as cancer, and autoimmune diseases ( Table 4 ). In cancer immunotherapy, targeting specific types of glycosphingolipids has been shown to modulate the immune microenvironments of tumors ( Yu et al ., 2020 ). Safingol and fingolimod are examples of sphinolipid analogues for clinical applications ( Choi and Song, 2020 ).…”
Section: Sphingolipidsmentioning
confidence: 99%
“…Generating high affinity binding ligands against GSLs is a notoriously difficult task due to the high structural flexibility of these molecules. An exception is the anti-GD2 antibody dinutuximab, which entered the market for the treatment of high-risk neuroblastoma patients [ 94 ].…”
Section: Therapeutic Deliverymentioning
confidence: 99%